Application of Wonosobo Sheep Fleece as a Material of Filler Jacket - Mustafa, Dody; Somantri, Karlina; Oktariani, Eka; Saifurohman, Saifurohman (Sainteks: Jurnal Sain dan Teknik, 2024)
The use of ducks down to serve as a filler in recent years has increased. In 2015, in Canada, the well-known jacket Company Canada Goose, which uses down as a filler, became very popular, even in 2016 its sales in the US grew by 50%. But the use of down is opposed by many parties including animal welfare groups (animal welfare) who campaign “save the duck” because the use of down is considered to hurt animals. Down is taken or uprooted from living birds without being given painkillers. Some companies then implement policies to ensure that the down used does not come from raw materials that hurt poultry. However, concerns about this still arise, because consumers will not be able to ascertain whether the down-fill jacket used is from Fluff plucked from living birds or not. In previous research, Wonosobo fleece has a thermal conductivity value of 0.03 W/moK, while the thermal conductivity of poultry fleece ranges from 0.024 – 0.03 W / moK. This shows that this fleece fiber has the potential to be used as an alternative raw material for jacket filler. In addition, Wonosobo sheep fur also comes from environmentally friendly materials, the process of epilation is done without hurting the sheep itself, it is the process of epilation of sheep have a positive impact on sheep, such as eradicating fleas on sheep fur. Based on the down issue and the potential of Wonosobo fleece to be used as a jacket filler, it is necessary to innovate the manufacture of multilayer jacket material made from fleece. Keywords: Dombos Fleece, Filler and Jacket